Representasi Stereotip Perempuan dalam Film "Tilik" Karya Agung Prasetyo (Analisis SemiotikaCharles Pierce) - Mescha Ayu Bernadette L Toruan (2022)
"Tilik" is a short movie directed by Wahyu Agung Prasetyo in collaboration with the Cultural Service of the Jogjakarta Provincial Government and produced by Rancavana Film and then uploaded to the Youtube channel on August 17, 2020 is a movie that tells about the behavior of a group woman who wants to visit the village head. This film has become a lot of discussion on social media because the script presented is very close and relevant to what happens in everyday life as woman are depicted during dialogue, especially woman who still swallow raw information obtained from the internet. This study aims to reveal how the representation of women in the short movie "Tilik" by Wahyu Agung Prasetyo. This research uses a qualitative approach with the semiotic analysis method of Charles Sanders Pierce. And as for the results of this study, the movie "Tilik" represents women who are contrary to the perspective of feminism because it still describes the patriarchal ideology that exists in women where women are depicted as submissive to their husbands, consider women unfit to be leaders, and how women show sensitive emotion, women who like to gossip, women who is misogyny, and women who is aggressive.